SOLAR ENERGY FOR DRYING AGRICULTURAL PRODUCTS - Shelimanova, E (Енергетика і автоматика, 2016)
The analysis of existing types of convective dryers using solar energy is given. The paper provides the design of atmospheric dryers, established on the basis of spring greenhouse, in which heat input is due to natural convection, is